Harmonization of the foreign policies of Turkey and the European Union: the case of the Middle East - Özcan, Mesut. (Thesis (Ph.D.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2007., 2007)
The aim of the dissertation is to analyze the impact of the European Union (EU) candidature on Turkish foreign policy and to the harmony and/or disharmony between Turkey’s and the European Union’s foreign policies regarding the Middle East. In this dissertation, by paying special attention to the political developments in the Middle East, Turkey’s relations with the European Union, and the evolution of the European Union in the post-Cold War period, I show to what extent the events in the post-Cold War era and Turkey’s candidature to the Union have brought the foreign policies of Turkey and the European Union closer and how Turkish candidacy for and possible membership in the European Union have increased and will increase this harmony. The analysis of the changes in the foreign policies of the EU members and candidates is referred as Europeanization. In order to compare Turkey with the other EU members and candidates, I touch upon the changes in the foreign policies of the EU member states and the theoretical framework to analyze this change and apply this frame work to the case of Turkey.